2017
DOI: 10.1016/j.pnpbp.2016.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and therapeutic potential of microRNAs in neuropsychiatric disorders: Past, present, and future

Abstract: Neuropsychiatry disorders are common health problems affecting approximately 1% of the population. Twin, adoption, and family studies have displayed a strong genetic component for many of these disorders; however, the underlying pathophysiological mechanisms and neural substrates remain largely unknown. Given the critical need for new diagnostic markers and disease-modifying treatments, expanding the focus of genomic studies of neuropsychiatric disorders to include the role of non-coding RNAs (ncRNAs) is of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 168 publications
(195 reference statements)
1
51
0
Order By: Relevance
“…Since then, there are numerous reports that revealed the roles of various miRNA in neuronal development and differentiation. The important functional roles of miRNA in neurogenesis, neuroprotection, survival, and pathogenesis of neuropsycho‐disorders have been also extensively studied and reviewed . In addition, alterations of miRNA are reported to be associated with many neuropsychiatric diseases.…”
Section: Mirna Biogenesis and Functions In The Cnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, there are numerous reports that revealed the roles of various miRNA in neuronal development and differentiation. The important functional roles of miRNA in neurogenesis, neuroprotection, survival, and pathogenesis of neuropsycho‐disorders have been also extensively studied and reviewed . In addition, alterations of miRNA are reported to be associated with many neuropsychiatric diseases.…”
Section: Mirna Biogenesis and Functions In The Cnsmentioning
confidence: 99%
“…The important functional roles of miRNA in neurogenesis, neuroprotection, survival, and pathogenesis of neuropsycho-disorders have been also extensively studied and reviewed. 7,[44][45][46][47][48][49] In addition, alterations of miRNA are reported to be associated with many neuropsychiatric diseases. For This phenotype is significantly rescued by transfection of miRNAs obtained from embryonic mouse midbrain, suggesting that miRNAs play essential roles in midbrain dopamine neuronal differentiation and survival.…”
Section: Mirna B I Og Ene S Is and Fun C Ti On S In The Cn Smentioning
confidence: 99%
“…The investigation of the role of miRNAs in normal and abnormal development of the central nervous system (CNS) revealed that more than half of all identified miRNAs were expressed in the brain and are involved in several biological processes in CNS development, including cell proliferation, cell differentiation, synaptogenesis, synaptic plasticity, and apoptosis [Alural, Genc, & Haggarty, ; Reschke & Henshall, ] and mutations in miRNA‐related genes and abnormal expression of miRNAs were found to be associated with several neurodegenerative diseases [Nelson, Wang, & Rajeev, ], including Alzheimer's Disease and Parkinson's Disease.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal expression of miRNAs has been reported in various tissues from patients with psychiatric disorders. Results regarding miRNA‐related genetic variants and abnormal expression of miRNAs have recently been reviewed for schizophrenia, bipolar disorder, and major depressive disorder [Alural et al, ; Hommers, Domschke, & Deckert, ] and, in spite of limitations such as population heterogeneity for genetic association studies and tissue specificity for expression profiling studies, point to several consistent findings (e.g. hsa‐miR‐137 for schizophrenia).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation